ANALISIS KEBUTUHAN KEPERIBADIAN CARL GUSTAV JUNG PADA TOKOH UTAMA SASA DALAM NOVEL LOVE EDELWISS AND ME KARYA MONICA ANGGEN - Yunis Sastika Putri; Aurellia Khairun Nissa; Eva Dwi Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
The aim of this research is that the researcher wants to analyze more deeply the conscious and unconscious personality dynamics of the main character in the novel entitled